Cholecystectomy in Patients with Liver Cirrhosis. (14th December 2015) - Strömberg, Jonas; Hammarqvist, Folke; Sadr-Azodi, Omid; Sandblom, Gabriel
Abstract : Background . The aim of this population-based study was to describe characteristics of patients with liver cirrhosis undergoing cholecystectomy and evaluate the risk for perioperative and postoperative complications during the 30-day postoperative period. Method . All laparoscopic and open cholecystectomy procedures registered between 2006 and 2011 in the Swedish Registry for Gallstone Surgery and ERCP (GallRiks) were included. Patients with liver cirrhosis were identified by linking data to the Swedish National Patient Registry (NPR). Results . Of 62, 488 patients undergoing cholecystectomy, 77 (0.12%) had cirrhosis, of which 29 patients (37.7%) had decompensated cirrhosis. Patients with cirrhosis were older and had more often gallstone complications at the time for surgery. Postoperative complications were registered in 13 (16.9%) patients with liver cirrhosis and in 5, 738 (9.2%) patients in the noncirrhotic group( P < 0.05 ) . Univariable analysis showed that patients with liver cirrhosis are more likely to receive postoperative blood transfusion (OR = 4.4, CI 1.08–18.0, P < 0.05 ) and antibiotic treatment >1 day (OR = 2.3, CI 1.11–4.84, P < 0.05 ) than noncirrhotic patients. Conclusion . Patients with cirrhosis undergoing cholecystectomy have a higher incidence of postoperative complications than patients without cirrhosis. However, cholecystectomy is safe and if presented with adequate indication, surgery should not be delayed due to fears of surgical complications.